Enlargement of main corneal incision: clinical intraindividual comparison of two preloaded intraocular lens injectors - Khoramnia, Ramin; Baur, Isabella; Łabuz, Grzegorz; Chychko, Lizaveta; Köppe, Maximilian; Hallak, Mustafa; Auffarth, Gerd U. (Journal of cataract and refractive surgery, 2023)
Purpose: - To compare the enlargement of the clear corneal incision from IOL implantation with 2 different intraocular lens (IOL) injectors: the AutonoMe preloaded with the Clareon IOL and the Multisert preloaded with the Vivinex IOL. - Setting: - The David J. Apple Center for Vision Research, Department of Ophthalmology, University of Heidelberg, Heidelberg, Germany. - Design: - Prospective randomized clinical comparative study. - Methods: - 96 eyes of 48 patients with cataract were intraindividually randomized to treatment with 1 of the 2 injectors. For Multisert eyes, the insert shield (IS) was used in the advanced position in 23 eyes. The initial incision was 2.2 mm, and intraoperative measurements of the incision size were made before and after IOL injection. 3 months postoperatively, keratometry and uncorrected (UDVA) and corrected (CDVA) distance visual acuities were assessed. - Results: - Results are reported for 96 eyes of 48 patients. The mean incision enlargement was 0.213 ± 0.068 mm in the Multisert with the IS group, 0.265 ± 0.055 mm in the fellow eyes (AutonoMe) (P < .05), 0.272 ± 0.060 mm in Multisert eyes treated without the IS, and 0.296 ± 0.066 mm for the fellow eyes (AutonoMe) (P > .05). The mean absolute surgically induced astigmatism was 0.42 ± 0.23 diopters (D), 0.50 ± 0.25 D, and 0.44 ± 0.18 D in the Multisert with the IS, Multisert without the IS, and AutonoMe group, respectively (P > .05). The UDVA and CDVA were comparable in all groups. - Conclusions: - The Multisert was associated with less wound enlargement than the AutonoMe. All groups had comparable functional outcomes. Therefore, the observed difference in incision enlargement may be of limited clinical relevance.
Gesehen am 14.12.2023